1987
DOI: 10.1002/cne.902660304
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of peptide‐ and amine‐containing neurones in motor, sensory, and autonomic regions of rat and human spinal cord, dorsal root ganglia, and rat skin

Abstract: The developmental patterns of neurofilament triplet proteins, peptide and amine immunoreactivities were compared in motor (ventral spinal cord), sensory (dorsal spinal cord, dorsal root ganglia, epidermis), and autonomic (intermediolateral cell columns, dermis) regions in the rat and human. In the rat, neurofilament triplet proteins first appeared in motoneurones (embryonic day 13). In the youngest human fetuses studied (6 weeks), immunoreactivity was present throughout the spinal cord. Peptides and amines occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
122
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(134 citation statements)
references
References 104 publications
12
122
0
Order By: Relevance
“…Of the cells in rat L4/ 5 DRG that express preprotachykinin (PPT) mRNA coding for SP, 78% are also positive for trkA, as shown by ISH, whereas no overlap exists with trkB and trkC expression (Kashiba et al 1996). During development, no SPimmunoreactive neurons are detected in rat DRG at E14.5, few positive cells are found at E19.5 and adult numbers are reached at birth (Hall et al 1997; see also Marti et al 1987).…”
Section: Neuropeptide Expression In Drgmentioning
confidence: 97%
“…Of the cells in rat L4/ 5 DRG that express preprotachykinin (PPT) mRNA coding for SP, 78% are also positive for trkA, as shown by ISH, whereas no overlap exists with trkB and trkC expression (Kashiba et al 1996). During development, no SPimmunoreactive neurons are detected in rat DRG at E14.5, few positive cells are found at E19.5 and adult numbers are reached at birth (Hall et al 1997; see also Marti et al 1987).…”
Section: Neuropeptide Expression In Drgmentioning
confidence: 97%
“…16,17 A prominent site of CGRP synthesis has been shown to be the DRG, which contains the cell bodies of primary afferent neurons that extend CGRPergic nerves to peripheral sites such as blood vessels. 19 In addition to neurogenic vascular responsiveness in the perfused mesenteric vascular beds, to clarify the effect of insulin resistance and chronic hyperinsulinemia on CGRPergic nerves activity, we investigated the content of CGRP in DRG isolated from control rats and FDR by an ELISA. Consequently, CGRP content in FDR (248.9 ± 25.1 pg ml -1 , Po0.05) was significantly smaller than that in age-matched control rats (358.4 ± 27.0 pg ml -1 ).…”
Section: Changes In Cgrp Content In the Drgmentioning
confidence: 99%
“…Morphological and functional studies have revealed a tremendous diversity of dorsal horn neurons (Christensen and Perl, 1970;Lima and Coimbra, 1986;Todd and Spike, 1993;Han et al, 1998;Grudt and Perl, 2002;Todd and Koerber, 2006). Diversity of the dorsal horn neurons is further suggested by the expression of neuropeptides, including the opioid-like peptides Dynorphin (DYN) and enkephalin (ENK), the anti-opioid peptide cholecystokinin (CCK), the tachykinin peptides Substance P (SP) and Neurokinin B (NKB), somatostatin (SOM), and others (Marti et al, 1987;Todd and Spike, 1993;Todd and Koerber, 2006;Polgar et al, 2006). Functionally, neuropeptides modulate the transmission of somatic sensory information, particularly those involved with pain perception (Kajander et al, 1990;Xu et al, 1993;Wang et al, 2001;Wiesenfeld-Hallin et al, 2002).…”
Section: Introductionmentioning
confidence: 99%